2022
DOI: 10.1039/d2cc02422e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies on the Cinchona anchored calixarene catalysed asymmetric Michael addition reaction

Abstract: Lower-rim Cinchona anchored calix[4]arene cationic catalysts were developed for asymmetric Michael addition of acetylacetone to β-nitrostyrenes. The desired Michael adducts formed with high yields and enantioselectivities. Density functional theory investigations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this letter, we wish to report noteworthy progress based on our initial investigations on the design of new α‐methylbenzylamine functionalized crown‐ether‐appended calix[4]arenes PTCs (V I and VII ) for asymmetric nitroaldol reaction with high yield (>99 %) and enantiomeric excess (99.8 %) under ambient conditions with a scant catalytic amount (0.1 mol %). Mechanistically, our studies suggested that calixarene‐anchored amines served as bifunctional catalysts via hydrogen bonding interactions with the Michael acceptor and donor through the N−H and phenolic oxygen, respectively [19] . With this understanding, we predicted that PTCs VI & VII could be able to favor the transition states involving aldehyde and nitromethanide during chirality transfer.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In this letter, we wish to report noteworthy progress based on our initial investigations on the design of new α‐methylbenzylamine functionalized crown‐ether‐appended calix[4]arenes PTCs (V I and VII ) for asymmetric nitroaldol reaction with high yield (>99 %) and enantiomeric excess (99.8 %) under ambient conditions with a scant catalytic amount (0.1 mol %). Mechanistically, our studies suggested that calixarene‐anchored amines served as bifunctional catalysts via hydrogen bonding interactions with the Michael acceptor and donor through the N−H and phenolic oxygen, respectively [19] . With this understanding, we predicted that PTCs VI & VII could be able to favor the transition states involving aldehyde and nitromethanide during chirality transfer.…”
Section: Resultsmentioning
confidence: 83%
“…Mechanistically, our studies suggested that calixarene-anchored amines served as bifunctional catalysts via hydrogen bonding interactions with the Michael acceptor and donor through the NÀ H and phenolic oxygen, respectively. [19] With this understanding, we predicted that PTCs VI & VII could be able to favor the transition states involving aldehyde and nitromethanide during chirality transfer. Additionally, selective binding of K + with crown ether generates chiral ion pairs, [20] augmenting enantioselectivities and rate of reaction (See Supporting Information for 39 K NMR).…”
Section: Resultsmentioning
confidence: 96%
“…[12][13][14][15] Calixarene core contains p-electronic conjugative systems with hydrophobic and hydrophilic sides, which provides a good platform for further functionalization by various groups and moieties to enhance the activity in various applications. 16 The literature presents several supramolecular LCs based on the calix [4]arene core, [17][18][19][20] however, very few display fluorescent properties. Previously, our research group reported fluorescent calix [4]arene functionalized LCs and explored their optical, gelation in OLED device fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the reactions of bromo derivatives 1 and 3 with cinchonidine in dry toluene at 100 °C delivered corresponding off-white crystalline VI and VII in excellent yields. Catalysts IV and V were synthesized via our recently reported procedure …”
mentioning
confidence: 99%
“…Catalysts IV and V were synthesized via our recently reported procedure. 27 Our studies started with an examination of asymmetric αalkylation of model substrate N-(diphenylmethylene)glycine ethyl ester 4a with benzyl bromide 5a to form optically active N-(diphenylmethylene)phenylalanine ethyl ester 6a. Initially, the catalysts I−VII were tested at 1 mol % catalyst loading in toluene (Table 1) using 50% aq NaOH at RT to afford the desired α-benzylated product 6a.…”
mentioning
confidence: 99%